Thermal Stability Characterization of PPy/Cl Conducting Polymer Using Inverse Gas Chromatography Technique - Ansari Khalkhali, R. (Asian Journal of Chemistry, 2016)
PPy/Cl was prepared chemically on the surface of reticulated vitreous carbon (RVC) as solid support. FeCl3 was used as oxidant for chemical oxidation of pyrrole monomer adsorbed on the surface of RVC particles. Thermal stability of PPy/Cl conducting polymer coated chemically on the surface of RVC as stationary phase and polarity changes with temperature were determined using inverse gas chromatography (IGC) technique.